- #1

- 78

- 0

ok so f(g(x)) = x, for all x.

f(3)=8

f'(3)=9

what are the values of g(8) and g'(8)

ok, so g(8) = 3

because f(g(8)) must equal 8, and f(3) = 8, so g(x) must equal three.

however, i have NO idea how to do g'(x)

i was thinking of using the chain rule, but this gets me nowhere..help!

f'(g(x))*g'(x) = 8 ?? is this correct?? then wouldn't g'(x) = 1 ??

f(3)=8

f'(3)=9

what are the values of g(8) and g'(8)

ok, so g(8) = 3

because f(g(8)) must equal 8, and f(3) = 8, so g(x) must equal three.

however, i have NO idea how to do g'(x)

i was thinking of using the chain rule, but this gets me nowhere..help!

f'(g(x))*g'(x) = 8 ?? is this correct?? then wouldn't g'(x) = 1 ??

Last edited: